Digital Literacy Crisis in Islamic Education: Managerial Unpreparedness in The Era of Technological Transformationtitle English - Nila Hanif Ulfiana; Finka Oktaviana Putri; Nur Anim Jauhariyah (ICO EDUSHA, 2025)
This study aims to analyze the digital literacy crisis in Islamic educational institutions amid the acceleration of global digital transformation. Using a literature review and critical theoretical analysis, the study explores various managerial factors influencing the implementation of digital technology in Islamic education, including digital leadership, internal policies, organizational culture, and evaluation systems. Data were collected from secondary sources comprising scholarly articles, academic books, policy reports, and national regulations relevant to education and digital transformation. The findings indicate that the digital literacy crisis is systemic in nature and is primarily caused by weak digital leadership, unclear policy directions, the absence of an institutional digital roadmap, and limited structured evaluation mechanisms. In addition, insufficient attention to pedagogical aspects, resistance within organizational culture, and unsustainable budget allocation further exacerbate the condition. This study concludes that strengthening digital literacy management through the integration of digital leadership into the organizational culture of Islamic educational institutions, accompanied by enhanced managerial capacity and the harmonization of technology with Islamic values, is a key strategy for ensuring sustainable digital transformation. Recommendations are addressed to leaders of Islamic educational institutions and policymakers to undertake managerial restructuring as a systematic effort to address the digital literacy crisis.